PENGARUH METODE OUTDOOR STUDY TERHADAP MINAT BELAJAR TEMA 6 KELAS V SD NEGERI 10 BETUNG TAHUN 2021/2022 - Okta Reza Lestari; Misdalina Misdalina; Ida Suryani (JS (JURNAL SEKOLAH), 2022)
Abstract : The Influence of outdoor study methods on interest in learning theme 6 class V SDN 10 Betung in 2021/2022. The formulation of the problem in this study “is there any effect of outdoor study method on interest in learning theme 6 for the five grade of SDN 10 Betung in 2021/2022” . so that finding the goal to find out whether or not there is an effect of outdoor study method on interest in learning. This research is qualitative research the type of quasi experimental method. The population in this reseach was all the five grade students which is totaling of 41 students. Nonequivalent control group design is used as a sampling method. This reseach used the “t”  test which obtained the result of 6,080 and 2,021 with a significant level of 5%. So that the hypothesis is accepted, with the conclusion that there is an effect of the outdoor study method on interest in learning theme 6 for the five grade students of SDN 10 Betung in 2021/2022.Keyword : Outdoor Study Methods, Minat BelajarAbstrak : Pengaruh metode outdoor study terhadap minat belajar tema 6 kelas V SDN 10 Betung tahun 2021/2022. Rumusan masalah pada penelitian ini “Apakah ada pengaruh metode outdoor study terhadap minat belajar tema 6 kelas V SDN 10 Betung tahun 2021/2022?”. Sehingga menemukan tujuan untuk mengetahui ada tidaknya pengaruh metode outdoor study terhadap minat belajar. Penelitian ini merupakan penelitian kuantitatif yang berjenis quasi eksperimental design. Populasi dalam penelitian ini adalah seluruh siswa kelas V yang berjumlah 41 siswa. Nonequivalent control group desing digunakan untuk pengambilan sampel. Penelitian ini menggunakan uji “t” yang memperoleh hasil  6,080 dan  2,021 dengan taraf signifikan 5%. Sehingga hipotesis diterima, dengan kesimpulan ada pengaruh metode outdoor study terhadap minat belajar tema 6 kelas V SD Negeri 10 Betung Tahun 2021/2022.Kata Kunci : Outdoor Study Methods, Minat Belajar